Pengaruh Penggunaan Media Video Sparkol Terhadap Motivasi Belajar Siswa Kelas IV SD Negeri Tidung - Syamsuryani Eka Putri Atjo; Muhammad Faisal; Yulanda Jesika Putri (STKIP Andi Matappa Pangkep, 2023)
This study is an experimental study that aims to determine the description of the use of sparkol videomedia, learning motivation, and the effect of the use of sparkol video media on learning motivation in grade IV students of SD Negeri Tidung. This type of research is quantitative research. The population amounted to 34 students. The data analysis technique used is hypothesis testing using t-test with the type of Independent Sample Test. Based on the observation sheet, it can be concluded that the learning process using sparkol video media goes very well. Based on the questionnaire of student learning motivation in the experimental class before being given treatment in the form of videomedia, sparkol was in the medium category, after being given treatment was in the high category. While the learning motivation of students in the control class before being given treatment in the form of image media was in the medium category, after being given treatment was in the medium category. Based on the results of inferential statistical analysis or hypothesis testing, it can be concluded that the use of sparkol video media has a significant effect on student learning motivation. significantly on student learning motivation.